2000
DOI: 10.1091/mbc.11.4.1305
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome Condensation Factor Brn1p Is Required for Chromatid Separation in Mitosis

Abstract: This work describes BRN1, the budding yeast homologue of Drosophila Barren and Xenopus condensin subunit XCAP-H. The Drosophila protein is required for proper chromosome segregation in mitosis, and Xenopus protein functions in mitotic chromosome condensation. Mutant brn1 cells show a defect in mitotic chromosome condensation and sister chromatid separation and segregation in anaphase. Chromatid cohesion before anaphase is properly maintained in the mutants. Some brn1 mutant cells apparently arrest in S-phase, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
87
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(101 citation statements)
references
References 28 publications
13
87
0
Order By: Relevance
“…It can be speculated that impaired association of condensation factors on hyperacetylated chromatin may alter the dissociation of cohesins during early mitotic stages, resulting in persistent cohesion along chromatid arms. The separin-dependent release of centromeric cohesins at anaphase onset would promote the formation of chromatin bridges between sister chromatids due to poor sister chromatid arm resolution, as already reported for condensin mutants (Bhat et al, 1996;Ouspenski et al, 2000, Steffensen et al, 2001 or after inhibition of sister chromatid decatenation by topoisomerase II inhibitors (Cimini et al, 1997). On the other hand, a lack of sister chromatid separation at the centromere level is clearly indicated by the observation of chromatin bridges spanning the centromeric region.…”
Section: Histone Hyperacetylation Prevents Sister Chromatid Resolutiosupporting
confidence: 64%
“…It can be speculated that impaired association of condensation factors on hyperacetylated chromatin may alter the dissociation of cohesins during early mitotic stages, resulting in persistent cohesion along chromatid arms. The separin-dependent release of centromeric cohesins at anaphase onset would promote the formation of chromatin bridges between sister chromatids due to poor sister chromatid arm resolution, as already reported for condensin mutants (Bhat et al, 1996;Ouspenski et al, 2000, Steffensen et al, 2001 or after inhibition of sister chromatid decatenation by topoisomerase II inhibitors (Cimini et al, 1997). On the other hand, a lack of sister chromatid separation at the centromere level is clearly indicated by the observation of chromatin bridges spanning the centromeric region.…”
Section: Histone Hyperacetylation Prevents Sister Chromatid Resolutiosupporting
confidence: 64%
“…Similar complexes exist in higher eukaryotes (Hirano et al, 1997;Schmiesing et al, 1998;Sutani et al, 1999;Freeman et al, 2000;Kimura et al, 2001). Dysfunction of any condensin subunit results in impaired mitotic and meiotic chromosome segregation (Strunnikov et al, 1995;Bhat et al, 1996;Freeman et al, 2000;Ouspenski et al, 2000;Hagstrom et al, 2002;Hudson et al, 2003;Ono et al, 2003;Cobbe et al, 2006).…”
Section: Introductionmentioning
confidence: 88%
“…Condensin complexes are structural components of mitotic chromosomes and play a central role in driving chromosome condensation Sutani et al, 1999;Ouspenski et al, 2000). In the Xenopus egg extract model the 13S condensin complex is required for ATP-dependent chromatin condensation .…”
Section: Introductionmentioning
confidence: 99%
“…Although all three 11S subunits are required for proper chromosome condensation and chromatid segregation (Sutani et al, 1999;Freeman et al, 2000;Lavoie et al, 2000;Ouspenski et al, 2000), the specific roles of each of the non-SMC subunits remain to be identified (Kimura and Hirano, 2000). Recently, Kimura and Hirano (2000) have proposed that XCAP-D2 and XCAP-G may participate in the activation of the XCAP-E and XCAP-C ATPases by a process directly involving their HEAT domains or by modifying the conformation of the SMC heterodimer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation